2019
DOI: 10.1111/adb.12711
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylcysteine yields sex‐specific efficacy for cue‐induced reinstatement of nicotine seeking

Abstract: Women report greater craving during certain phases of the menstrual cycle. As well, research indicates that pharmacotherapies for smoking may be less efficacious in women compared to men, which may be due to interactions with natural fluctuations in ovarian hormone levels. N-Acetylcysteine (NAC) is a glutamatergic compound that has shown some efficacy in treating substance use disorders and aids in the prevention of relapse. However, it is unclear whether NAC has sex-specific effectiveness for nicotine relapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 80 publications
0
24
1
Order By: Relevance
“…1) on a fixed ratio-1 (FR-1) schedule of reinforcement nicotine was delivered during a 5.9-s infusion after a lever press on a designated active lever. Concurrent with each infusion, cue lights located above the levers were illuminated and a tone (2900 Hz) was presented, followed by a 20-s timeout period during which additional lever presses were recorded by had no programmed consequences (Goenaga et al 2019;Powell et al 2019;Gipson et al 2013a, b). An inactive lever was present at all times and presses on this lever were recorded but produced no programmed consequences at any time during the experiment.…”
Section: Self-administration Extinction and Reinstatement Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…1) on a fixed ratio-1 (FR-1) schedule of reinforcement nicotine was delivered during a 5.9-s infusion after a lever press on a designated active lever. Concurrent with each infusion, cue lights located above the levers were illuminated and a tone (2900 Hz) was presented, followed by a 20-s timeout period during which additional lever presses were recorded by had no programmed consequences (Goenaga et al 2019;Powell et al 2019;Gipson et al 2013a, b). An inactive lever was present at all times and presses on this lever were recorded but produced no programmed consequences at any time during the experiment.…”
Section: Self-administration Extinction and Reinstatement Proceduresmentioning
confidence: 99%
“…1b). Extinction criteria were the same as those used in prior studies (Powell et al 2019;Goenaga et al 2019), where active lever pressing was below 30 presses and was significantly reduced compared to session one of extinction training.…”
Section: Nicotine Self-administration and Extinctionmentioning
confidence: 99%
“…Administration of N -acetylcysteine combined with an appropriate psychotherapy has been shown to be clinically effective in the treatment of the tobacco use disorder ( Prado et al, 2015 ), while several preclinical studies have shown that N -acetylcysteine inhibits cue-induced nicotine reinstatement ( Ramirez-Nino et al, 2013 ; Powell et al, 2019 ; Goenaga et al, 2020 ; Moro et al, 2020 ; Namba et al, 2020 ). Noteworthily, such an effect of N -acetylcysteine was blocked by microinjection of a GLT-1 antisense morpholino into the nucleus accumbens ( Namba et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, at present, it is unknown which the molecular fraction of the drug is, that correlates with its pharmacological effects (Samuni et al, 2013). Moreover, several papers have recently reported sex differences in the psycho‐pharmacological effects of NAC under different indications and experimental paradigms (Goenaga et al, 2020; Monte et al., 2020). Hence, following the pipeline to the clinical evaluation of its alcohol anti‐relapse effect, it would be highly recommended to previously elucidate its molecular mechanism of action, to determine plasma NAC levels that correlate with their pharmacological response as well as to evaluate different NAC treatment regimens and doses focusing on the sex and gender differences previously reported for this drug.…”
Section: Discussionmentioning
confidence: 99%